TANGGUNGJAWAB NOTARIS DALAM PENDAFTARAN JAMINAN FIDUSIA SECARA ELEKTRONIK (ONLINE) MENURUT PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA DI KANTOR NOTARIS MHD. AFANDI MUARO BUNGO - Dwikornida dan Ihda Fitria (Fakultas Hukum Universitas Tamansiswa Padang, 2020)
One of the roles of the notary is to serve the interests of the parties, for example, in helping to make a loan agreement. If a debt agreement is burdened with collateral that is only for movable objects, a fiduciary agreement arises as an accecoir agreement whose existence always follows the principal agreement. The responsibility of a notary public in registering fiduciary guarantees electronically (online) is to make a fiduciary guarantee deed, and register a fiduciary guarantee deed until the issuance of a fiduciary guarantee certificate by the fiduciary guarantee registration office. Since March 2013, in line with the enactment of ministerial regulation No. 9 of 2013 concerning the enactment of electronic fiduciary guarantee registration, fiduciary guarantee registration is no longer done manually but by online through the websie director general for registration of fiduciary guarantees.